2017
DOI: 10.1080/15228959.2017.1319317
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Our Troops: Library Services and Support for Veterans

Abstract: Veterans are a unique population that can be found in libraries across the United States. Libraries of all types are developing new approaches to the veterans in their patron populations in the wake of the wars in Iraq and Afghanistan. This study identifies several common strategies that libraries, especially public and academic libraries, are employing to support their patrons who are veterans, as well as distinctions in strategy according to library type. It further explores whether libraries are relying upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For example, research has indicated that academic libraries have increasingly begun to assign student veterans their own library liaison. 6 However, targeted library support for veterans is far from ubiquitous. Research suggests that libraries providing this type of support are likely to have a staff member who has close ties to the veteran and military communities.…”
Section: Programming and Services For Student Veteransmentioning
confidence: 99%
“…For example, research has indicated that academic libraries have increasingly begun to assign student veterans their own library liaison. 6 However, targeted library support for veterans is far from ubiquitous. Research suggests that libraries providing this type of support are likely to have a staff member who has close ties to the veteran and military communities.…”
Section: Programming and Services For Student Veteransmentioning
confidence: 99%
“…LeMire's article, "Supporting Our Troops: Library Services and Support for Veterans," is unusual because she not only examines current trends in library outreach but also includes the veterans who are library employees in her discussion of how veterans themselves are included or excluded in library outreach efforts. 8 LeMire wisely used her status as a veteran as an entrée into the population.…”
Section: Veteran Views Of the Librarymentioning
confidence: 99%